(untitled) (The Research of Medical Science Review, 2025)
BACKGROUND: Fungal urinary tract infection (FUTI) is a growing concern among patients with chronic illnesses, yet its risk factors remain incompletely understood. OBJECTIVE: To determine the frequency of urinary fungal infection among decompensated chronic liver disease patients. METHODOLOGY: This cross-sectional study included 148 patients, comprised 148 DCLD subjects were explored for urinary fungal infection. Associations between FUTI and variables such as age, gender, Child-Pugh class, obesity, and disease duration were assessed using chi-square tests, with p < 0.05 considered significant. RESULTS: The urinary fungal infection was observed in 90 (60.8%) subjects. The FUTI prevalence was highest in the 18-29 and 60-70 year groups (22.2% each), but no statistically significant association was observed with age (p=0.70). Gender showed a strong association (p<0.01), with females comprising 73.3% of cases. Child-Pugh classification was significantly related to FUTI (p<0.01), with Class B patients more frequently affected (70.0%) than Class C (30.0%). Obesity was also significantly linked to FUTI (p<0.01), with 67.8% of obese individuals infected. Disease duration showed no significant association (p=0.87). CONCLUSION: Female gender, obesity, and Child-Pugh Class B were significantly associated with FUTI in chronic liver disease patients, whereas age and disease duration were not. Targeted screening and preventive measures for these high-risk groups may help reduce infection burden.